Manufacturing and toughening effects on the material properties of wind turbine blade adhesives. (December 2022) - Srinivasan, Dharun Vadugappatty; Vassilopoulos, Anastasios P.
Abstract: Hybrid adhesives can be developed using commercially available adhesive materials and customized to the required loading conditions. In this paper, SPABOND™ 820HTA (non-toughened) and SPABOND™ 840HTA (toughened) adhesives are hybridized by two strategies and fabricated by machine and manual mixing methods. The manufacturing and hybridization effects on the bulk adhesive properties are evaluated by dynamic mechanical analysis, quasi-static tensile, V-notch shear and single-edge-notch bending tests. X-ray micro-computed tomography, digital image correlation technique, high speed camera and scanning electron microscopic images are used for assessing the manufacturing quality, computing the full-field displacement and strain, and failure analysis. By considering the manufacturing methods, the measured properties are less influenced by the presence of voids but dependent on the glass fiber filler orientation. The adhesive toughening method improves the strain to failure and tensile toughness, decreases the strength and modulus and no significant effect on the glass transition temperature. Highlights: Developed hybrid adhesives using Spabond 820 and Spabond 840 wind turbine adhesives. Specimens manufactured through machine dispensing and manual hand mixing methods. Exploited micro-computed tomography, DIC, SEM and high-speed imaging techniques. Evaluated and compared the DMA, tensile, shear and fracture toughness properties. BTM1 hybrid adhesive is commercialized as Spabond 830 adhesive.